Participation and clarity of budget targets, management accounting information system on managerial performance with budgetary slack as a mediation variable - Wigati, Retno; Rustiana, Siti Hamidah; Dyarini, Dyarini (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2024)
The aim of this research is to analyze "budget participation, clarity of budget targets and management accounting information systems on managerial performance with the budgetary slack as a mediating variable," which has been carried out by 5 service companies affected by COVID-19. This research uses quantitative methods, and the data source used is primary data. The population in this research is 5 service companies spread across Jakarta, including PT. Sukses Andalan Bangsa, PT. Anak Bangsa Cakrawala Dunia, PT. Impact Power Mandiri, PT. Kitamuda Andalan Indonesia and PT. Triputra International. The sample selection for this research included directors, managers, and supervisors in each division of the company, with a total of 50 respondents. In this research, data analysis uses SmartPLS 4.0 with a data-based analysis method structural equation modeling based on partial least. Based on the hypothesis testing carried out, the research results show that budget participation has no positive and insignificant effect on managerial performance. For clarity of budget targets and management, accounting information systems have a positive and significant effect on managerial performance. Then, the budget gap has a positive and significant mediating effect on all variables of budget participation, clarity of budget targets, and management accounting information systems on managerial performance.